2014
DOI: 10.1007/s10439-014-1215-1
|View full text |Cite
|
Sign up to set email alerts
|

Artery Remodeling Under Axial Twist in Three Days Organ Culture

Abstract: Arteries often endure axial twist due to body movement and surgical procedures, but how arteries remodel under axial twist remains unclear. The objective of this study was to investigate early stage arterial wall remodeling under axial twist. Porcine carotid arteries were twisted axially and maintained for three days in ex vivo organ culture systems while the pressure and flow remained the same as untwisted controls. Cell proliferation, internal elastic lamina (IEL) fenestrae shape and size, endothelial cell (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…This system is at least somehow comparable to our ACM. However, effects of altered flow conditions have only been investigated in human saphenous veins after coronary artery bypass grafting [13]. Mundagi et al also reported on an ex vivo bioreactor that allowed an evaluation of cellular interactions in the carotid artery of pigs under controlled physiologic conditions [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system is at least somehow comparable to our ACM. However, effects of altered flow conditions have only been investigated in human saphenous veins after coronary artery bypass grafting [13]. Mundagi et al also reported on an ex vivo bioreactor that allowed an evaluation of cellular interactions in the carotid artery of pigs under controlled physiologic conditions [2].…”
Section: Discussionmentioning
confidence: 99%
“…Various models have recently been developed to understand vascular biology, Among those are ex vivo tissue culture systems described to evaluate vascular responses in relation to various biomechanical and biochemical factors [12,13]. So far, few efforts have been taken to exploit the potential of ex vivo vessel bioreactors towards a high-fidelity ex vivo replication of the hemodynamic factors affecting arterial wall behavior in an artificial environment.…”
Section: Introductionmentioning
confidence: 99%
“…The lumen and outer diameters of the medial layer, as well as the intima-media wall thickness were measured. The wall thickness to lumen diameter ratio was then determined (Han and Ku 2001; Wang et al 2015). The collagen and elastin contents were quantified as the ratio of the area occupied by collagen and elastin fibers divided by the total area of the media, respectively, and the collagen to elastin (C/E) ratio was calculated as an index of arterial (medial wall) stiffness (Jones et al 2009; Zhang et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…After the animals were sacrificed, the left carotid arteries were harvested, cut into 5 μm frozen slides as described above and processed for BrdU staining (Wang et al 2015). Cell proliferation was quantified by the ratio of the proliferating cells to counterstained all vascular cells (Xiao et al 2014; Wang et al 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation